Habitual Nocturnal Sleep, Napping Behavior, and Recovery Following Training and Competition in Elite Water Polo: Sex-Related Effects - Koutouvakis, N.G.; Geladas, N.D.; Mouratidis, A.; Toubekis, A.G.; Botonis, P.G. (International Journal of Sports Physiology and Performance, 2024)
Purpose: To examine nocturnal sleep patterns, napping behaviors, and subjective wellness responses of elite water polo players within an in-season week and to identify whether sleeping patterns differ between men and women. Methods: Sleep characteristics of 10 male and 17 female professional water polo players were objectively assessed during 1 week of the in-season period, including 5 training days, 1 match day, and 1 day of rest. Internal load (rating of perceived exertion × duration of training or match) was assessed 30 minutes posttraining or postmatch, and the total quality of recovery was recorded every morning. A series of multilevel models were used to analyze the data. Results: Time in bed and wake-up time were earlier on both training (P < .001) and rest days (P < .001) than on the day of the match. Internal workload did not predict any of the players' sleeping patterns. Midday naps predicted less time in bed (P = .03) and likely less sleep time (P = .08). The total quality of recovery was predicted only by the total sleep time (P < .01).Women exhibited higher sleep efficiency (P < .001), less waking after sleep onset (P = .01), and a lower number of awakenings (P = .02) than men. Conclusions: The current results indicate that the nocturnal sleep patterns of elite water polo players are not associatedwith internal load and thatwomen display better nocturnal sleep quality compared with men. As long naps interfere with nocturnal sleep, and total nocturnal sleep time predicts total quality of recovery, we suggest that athletes follow hygiene sleep strategies to facilitate adequate nocturnal sleep and next-day recovery. © 2024 Human Kinetics Publishers Inc.. All rights reserved.
Keywords: Adult; arousal; article; athlete; Athletes; Behavior; cohort analysis; Competition; competitive behavior; duration; Exercise; Female; human; human experiment; Humans; Kinetics; Male; male and female athletes; night sleep; nighttime sleep; normal human; Physical Conditioning, Human; physiology; procedures; sex; sex factor; Sex Factors; Sleep; sleep efficiency; sleep pattern; sleep quality; sleep time; stage 1 sleep; team sport; team sports; time factor; Time Factors; time in bed; training; wake up time; wakefulness; water polo; water sport; Water Sports; Workload; Young Adult